Banjar Ulama Traditions in South Kalimantan - M. Ihsan Fauzi (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2023)
This article discusses the tradition of scholarship among the Banjar people in South Kalimantan. As the majority group, the Muslim followers of the Banjar ethnic group in South Kalimantan are closely tied to the role of scholars (ulama) in the dissemination of Islam, especially within the Banjar community. It is not surprising that the title given to a scholar includes the term 'tuan guru haji' (master teacher of the pilgrimage). Such titles are bestowed upon individuals who have studied religious knowledge in the Haramain or the Middle East, following the educational tradition of Banjar scholars oriented towards Sheikh Muhammad Arsyad al-Banjari. Based on this foundation, this article aims to answer the question of how the Banjar tradition of scholarship fulfills its role in propagation (Dakwah). Through a qualitative approach, this research understands that religious lectures within the Banjar scholar's Dakwah tradition have become the most popular means of spreading Islamic teachings. In practice, scholars are not only considered preachers but also educators, leaders, and guides in worship. In this context, scholars play a central role in the lives of the Banjar community, and it is believed that they can address various challenges in life.